EXTENSIVE READING IN L2 LEARNING: CURRENT TRENDS AND FUTURE POSSIBILITIES - Made Frida Yulia (Premise: Journal of English Education and Applied Linguistics, 2018)
Due to the minimum language exposure that EFL learners have, one recommended way to promote interest in foreign language reading is through Extensive Reading. This kind of reading has gained popularity over the years, ever since it was introduced to the realm of foreign language learning. Extensive Reading has been shown to bring a lot of benefits for L2 learners in many respects, and, consequently, it has been implemented in a variety of contexts. This article aims at revisiting Extensive Reading along with its pertaining principles. In addition, it attempts to scrutinize a number of recent studies conducted in the area of Extensive Reading to discover current trends and possible areas which are open for further exploration.